Masticatory function between chewing with and without wearing clear thermoplastic appliances - Rungtiwa Jirawiwatsaree; Chidsanu Changsiripun (BMC, 2024)
Abstract Background Clear thermoplastic materials are used in a variety of oral appliances. In some situations, patients may wear clear thermoplastic appliances while eating. However, the effect of wearing clear thermoplastic appliances on chewing efficiency is unknown. This study aimed to evaluate the differences in masticatory function between chewing with and without wearing clear thermoplastic retainers over a 6-month period, and its associated factors. Methods Thirty patients who received upper and lower clear retainers after debonding fixed appliances were examined for objective and subjective masticatory function at retainer delivery (T0), 3-month (T1), and 6-month follow-ups (T2) in two conditions: with and without wearing their retainers while chewing. The objective method used multiple sieves reported as the median particle size (MPS). The food intake ability (FIA) test served as the subjective method. Paired t-test was used to compare the outcomes between chewing with and without retainers at each evaluation time point. Repeated measures ANOVA followed by the Bonferroni post-hoc test was used to compare the outcomes between the three evaluating time points. Multivariable linear regression analysis was performed to assess whether age, sex, and extraction/non-extraction was associated with these effects. Results The MPS was significantly greater when chewing with retainers compared with chewing without them at T0 (P < 0.05), however, it was not significantly greater at T1 and T2 (P > 0.05). The MPS with and without the retainers tend to decrease between T0, T1 and T2. In particular, the MPS while chewing with retainers significantly decreased between T0 and T1. The total FIA score and FIA subscores for hard and soft food were significantly lower when eating with retainers at T0 (P < 0.05), however, all FIA scores when eating without retainers did not significantly change between T0, T1, and T2. No significantly associated factors were identified. Conclusions Wearing clear retainers while chewing decreases objective and subjective masticatory function immediately after completing orthodontic treatment. However, this significantly improved to levels comparable to chewing without retainers after a 3-month follow-up. Age, sex, and extraction/non-extraction treatment were not associated with the difference in masticatory function while chewing with and without wearing the retainers.